English Narratives in Conflict: Analyzing the Representation of the Palestinian Struggle in Al Jazeera and Western News Media - Nour T. M. Alhaj; Siti Sarah Fitriani; Kismullah Abdul Muthalib; Iskandar Abdul Samad (AT-TA'LIM, 2025)
This study compares media coverage of the Palestinian-Israeli conflict between Al Jazeera and Western media outlets such as the BBC, CNN, and The New York Times. The study aims to discover viewpoint gaps between Palestinian and Western news coverage, assess the role of Aljazeera local reporters in promoting world awareness, and investigate biases in media stories from both sides. A qualitative content analysis examined 14 news articles—seven from Al Jazeera and seven from Western sources—that covered significant events during the 2023-2024 Gaza conflict. The study examined variations in how conflict-related events are portrayed, language usage, and narrative framing. The findings show essential differences in viewpoint between Al Jazeera and Western media. Al Jazeera's reporting is typically more humane and passionate, highlighting Palestinian suffering and placing blame for violence on Israeli troops; in contrast, news from Western media tends to be largely ignorant of the sufferings of the innocent Palestinians who continue to become victims of endless indiscriminate bombings. Moreover, Aljazeera local reporters are essential in influencing attitudes worldwide because they provide personal stories of the war in contrast to Western media's more detached, objective reporting style. These results emphasize the significance of comprehending media bias and viewpoint gaps in conflict reporting and draw attention to the particular contribution that local reporters make in offering a more thorough analysis of the Palestinian-Israeli conflict.